ASSESSMENT OF CHANGES IN QUALITY OF PREHOSPITAL TREATMENT OF PATIENTS WITH ACUTE CORONARY SYNDROME IN THE LAST FEW YEARS: LIS-1 VS LIS-3 REGISTRIES - Yu. V. Semenova; A. V. Zagrebelnyy; N. P. Kutishenko; M. L. Ginzburg; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
Aim. To assess the changes in prehospital treatment of patients with acute coronary syndrome during the last years on the basis of the LIS-3 registry data.Material and methods. Data of acute coronary syndrome hospital registry LIS-3 (2013-2015, n=397) and acute myocardial infarction hospital registry LIS-1 (2005-2007, n=1133) were used. To assess quality of prehospital treatment the fact of taking specific pharmacological groups of medications for primary and secondary cardiovascular diseases prevention was taken into consideration.Results. Patients in the LIS-3 registry, in comparison with patients in the LIS-1 registry, more often took antiplatelet drugs (23.2% vs 15.7%, respectively; p<0.01) and statins (4.9% vs 2%, respectively; p<0.01). However, in general, the frequency of prescribing these groups of medications remained low. The use of medications of other pharmacological groups was comparable in patients of LIS-1 and LIS-3 registries (p>0.05). The quality of prehospital treatment did not differ significantly in survived and deceased patients of LIS-3 registry (p>0.05).Conclusion. Only slight improvement in the quality of prehospital therapy in patients with acute coronary syndrome was revealed, mainly due to more frequent use of antiplatelet drugs and statins. It may be explained by poor detection of early forms of ischemic heart disease and underestimation of the importance of risk factors correction, both on the part of patients and on the part of physicians.